Happiness: Towards a philosophical approach to economic wealth - ZOHEIR Ahmed; EL Arabi Abderahman (المجلة الأفروآسيوية للبحث العلمي, 2024)
Like all knowledge, wealth in economics poses problems of genesis, identification, scientific, representation, scope, and so on. To study the complexity of this paradigm and, eventually, to demystify it, we need to place it within different disciplinary fields. This interdisciplinarity consists of deciphering the inner workings of this conceptual and representational alchemy of intangible capital.Similarly, research into happiness as economic wealth is still in its infancy. There is still no unanimously accepted philosophical or scientific construct. From a conceptual point of view, happiness is a paradigm that coagulates a multitude of designations, to the point where it is complex to analyze it from a philosophical, epistemological, and historical perspective. Studying the history of the genesis of economic happiness requires us to call on the disciplines that drive this approach, in particular philosophy. This disciplinary field would enable us to assimilate the archaeology of philosophy and, ultimately, the intellectual trajectory of our knowledge to demystify the complexity of economic wealth from a purely philosophical angle. Our article attempts to answer the following question: To what extent does happiness constitute a complex object of study for wealth creation?